Pelaksanaan Bedside Handover terhadap Komunikasi Interprofesional Perawat - Nurul Hidayah; Bustami Syam; Nurmaini Nurmaini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of bedside handover implementation on nurse interprofessional communication at Cut Meutia General Hospital. The research used a quasi-experimental method with a nonequivalent control two-group pre-post test design. The results showed an effect of bedside handover on interprofessional communication at the Cut Meutia General Hospital ((p=0.001 <0.05). In conclusion, the performance of bedside handover affected the nurse's interprofessional communication, among others, in conveying information and discussions, receiving information, respecting the uniqueness of nurses, and better teamwork. Keywords: Bedside Handover, Nurse Interprofessional Communication